Nurturing time in nature: Lessons from waldkindergarten - Ferraro, M. (Educational Research and the Question(s) of Time, 2024)
Nature-based education has been increasingly recognized as a socially responsible approach to nurture curiosities in the hands, heads, and hearts of children. Research in the last ten years suggests that children who attend forest preschools, as opposed to traditional preschools, demonstrate growth in all domains of early childhood development. Domains include cognitive growth, executive functioning, physical development, linguistic proficiency, and socio-emotional well-being. In addition to cultivating these areas two Waldkindergarten or forest schools, studied in this chapter nourish as additional component—connectedness, compassion, and care for nature. There has been a steady increase in nature-based preschool programs as alternative approaches to traditional, indoor classrooms. With the expansion of programs, globally, and heightened awareness around environmental issues in the Anthropocene, nature-based education is increasingly recognized for cultivating socially responsible approaches that yield sustainable practices. This chapter reports on an exploratory study that synthesized two fieldwork experiences in German Wald-kindergarten, one in the north near Denmark and one in south, near the foothills of the Alps. Through a qualitative, thematic analysis of fieldnotes of direct and partici-pant observation, interviews with facilitators and analysis of student-created artifacts, this chapter explores how time in nature can be reconceived as a space to cultivate a connectedness to nature that fosters a commitment to conservation and sustain-ability. Primary goals of this research are to identify practices that center children learning with nature and, subsequently, to reconceptualize forest school practices in contexts outside of northern Europe. This research interrogates ways in which forest schools serve as spaces to engage in work around environmental stewardship while problematizing the accessibility of nature-based programs. Whilst reflecting upon lessons from Waldkindergarten, this chapter explores how nature-based Education provides opportunities towards a sustainable future for cultivating children’s curiosities in timeless traditions. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.
Keywords: Connectedness to nature; Environmentally sustainable pedagogy; Forest schools; Nature preschool; Nature-based education; Waldkindergarten; dept.cur; peer-reviewed

“Constant dropping wears away a stone”: Chinese international women instructors’ duoethnography on advancing racial equity - Wang, P.; Huang, T. (International Journal of Qualitative Studies in Education, 2024)
Faculty of color are constantly experiencing trauma and racial inequities in inherently Eurocentric educational spaces where their histories, knowledge, and experiences are delegitimized and marginalized. Employing critical race feminism (CRF) and White racial identity development model, this article details ways in which two Chinese international women instructors grappled with tensions and trauma and celebrated (small) joys and successes within Predominantly White Institutions (PWI) in the United States. We drew on duoethnography, a dialogic methodological approach grounded in social justice, to make meaning of, (re)construct, and advance racial equity in pedagogy. We examined and analyzed four sources of data: our personal narratives, transcripts of eight Zoom meetings, reflection journals, and informal conversational exchanges. We identified three strategies for navigating dissonance and conflicts: 1) being vulnerable, 2) recognizing shared and differing marginalization or privileges, and 3) building allies intentionally and strategically. © 2024 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Chinese international women instructors of color; dept.cur; duoethnography; peer-reviewed; racial equity

Academic bullying as a racialized phenomenon in STEM higher education: Centering the experiences of Asian international doctoral students - Wang, Peiwen (Journal of International Students, 2024)
While students of color’s experiences of academic bullying from their advisors have been documented in the literature (e.g., Moss & Mahmoudi, 2021), little is known regarding the role that race plays in the normalization and perpetuation of academic bullying within higher education. Utilizing Asian critical theory (AsianCrit) as both the theoretical and analytical lens, this phenomenological study centers five STEM Asian international doctoral students’ experiences of academic bullying through semi-structured interviews. It is found that racialized academic bullying is operationalized by a) legitimizing exploitation through racializing discourses; b) maintaining White supremacy across transnational contexts; and c) intersecting systems of oppression. Implications and recommendations are offered as to what stakeholders can do collectively to address racialized academic bullying towards minoritized students and to combat systemic inequities and oppression.
Number: 4
Keywords: STEM; dept.cur; peer-reviewed

Planning for Equitable Student Sensemaking: An Examination of Preservice Teachers Noticing of Elementary Science Lesson Plans - Benedict-Chambers, A.; Sherwood, C.-A. (Journal of Science Teacher Education, 2024)
Designing and analyzing lesson plans is a ubiquitous practice in teacher education, and yet we know little about how preservice teachers (PSTs) notice elements of their lesson plans that afford opportunities for supporting equitable student sensemaking. We investigate how the use of a tool, a framework for supporting equitable sensemaking, guided 36 PSTs to notice four features of equitable sensemaking in their plans. Qualitative analysis of PSTs’ comments about their plans generated a coding rubric and three associated levels for noticing. These levels included (1) paying little to no attention to explicit strategies and making assumptions about the ways that traditional classroom practices might facilitate equitable sensemaking; (2) attending to some strategies but providing few details; and (3) attending to and making connections between specific moves and broader principles and practices of supporting equitable student sensemaking. Guided by the tool, PSTs were able to provide elaborate details about their plans to design instruction to engage students in authentic scientific work focused on investigating and explaining phenomenon (feature 4) and to position students as knowers (feature 2), but they struggled to discuss explicit ways to leverage students’ lived experiences in their science lessons (feature 3) and facilitate equitable engagement and participation (feature 1). This suggests that even with the use of a tool, it may be challenging for PSTs to attend to and describe in detail strategies for leveraging students’ out-of-school lives and interests for science learning and explicit classroom strategies for making learning accessible and engaging for all. © 2024 Association for Science Teacher Education.
Keywords: Equitable science instruction; dept.cur; methods courses; noticing; peer-reviewed; preservice teachers